Bo diplomacija Evropske unije nadomestila nacionalne diplomacije v tretjih državah? - Udovič, Boštjan (Teorija in praksa, 2019)
The article deals with the issue of merging national embassies and EU delegations in third countries. The idea behind the article is to test the notion that European diplomatic delegations can replace national embassies in third countries. A survey conducted among national diplomats of EU member countries residing in Slovenia does not confirm this notion. Moreover, what emerges is that at this stage of European Union integration it is impossible to conceive of such a step since that would be "too much too soon", meaning that a mere shift towards a more progressive European integration could trigger a discussion on merging embassies and EU delegations abroad.
Keywords: Ambassadors; Diplomacija; Diplomacy; European union; Evropska unija; Foreign policy; gospodarska diplomacija; International cooperation; Mednarodno sodelovanje; Veleposlaniki; Zunanja politika